Preparation of hydrophilic luffa sponges and their water absorption performance. (20th August 2016) - Liu, Zhi; Pan, Yanxiong; Shi, Kai; Wang, Weicai; Peng, Chao; Li, Wei; Sha, Di; Wang, Zhe; Ji, Xiangling
Highlights: Hydrophilic luffa sponges are prepared successfully via grafting polymerization. Fibers were characterized by different techniques. The alkalization conditions, the grafting conditions, water absorption kinetics, and absorption capacities are investigated extensively. The absorption mechanism is also discussed. Abstract: Hydrophilic luffa sponges are prepared by grafting polymerization of acrylamide (AM) on luffa cylindrica and subsequent partial hydrolysis under alkaline conditions. Attenuated total reflection infrared spectroscopy is used to verify the composition of the grafted (luffa- g -PAM) and hydrolyzed (luffa- g -(PAM- co -PAANa)) samples. Alkalization conditions, including aqueous NaOH concentrations, alkalization temperature, and time, are studied extensively. Optimized conditions are then obtained. The grafting percentage (GP) of polyacrylamide increases with the feed ratios of [AM]/[OH] and [Ce]/[OH], reaction temperature, and time. Furthermore, the GP can reach up to 160%. Pristine, alkalized, grafted, and hydrolyzed luffa sponges show rapid absorption kinetics, and the pseudo second-order rate equation is applied to describe their kinetic procedure. Reaction conditions, such as [AM]/[OH], [Ce]/[OH], reaction temperature and time, influence the water absorption capacities of grafted and hydrolyzed samples. The hydrolyzed luffa sponges particularly exhibit high water absorption capacities of 75 g g −1 . The absorption mechanism is also discussed.